Priority research questions in global peatland science - Milner, Alice M.; McKeown, Michelle M.; Ruwaimana, Monika; Gallego-Sala, Angela; Loisel, Julie; Menges, Johanna; Roland, Thomas P.; Ahiable, Crystal A. E.; Akwany, Leonard O.; Alarcon-Prado, Paola; Anshari, Gusti; Alappat, Linto; et al. (Springer Nature, 2026)
Peatlands are among Earth’s largest terrestrial carbon stores and are crucial for climate regulation, biodiversity conservation, and water security. Yet peatlands worldwide are deteriorating under pressures from climate change and human disturbance. Strategic, globally coordinated research is urgently needed to protect, restore and manage peatlands so they can continue to deliver essential ecosystem services. To meet this challenge, here we present a global research prioritisation for peatland science, based on a two-stage online survey and expert voting exercise involving 467 participants from 54 countries. We identify 50 priority research questions spanning carbon dynamics, climate impacts, restoration and management, technological innovation, and community and policy engagement. These questions provide a community-informed agenda to guide peatland research over the next decade. Addressing them will help close critical knowledge gaps, strengthen evidence-based decision making, and support the role of peatlands in achieving global climate and biodiversity goals.
Keywords: environmental sciences; scientific community; peatlands